IMMUNOPATHOLOGICAL CHANGES OF STAPHYLOCOCCUS AUREUS EXPERIMENTAL INFECTION IN MICE IMMUNIZED WITH FOOT AND MOUTH DISEASE VACCINE - Sura A. Radam (The Iraqi Journal of Agricultural science)
The present study was carried out to investigate immunopathological effect of foot and mouth disease vaccine against nosocomial infections, to achieve this goal different samples obtained from urine of hospitalized patient, the isolated bacteria were identified by cultural examination,  biochemical tests PCR. Twenty-four  mice were divided equally into three groups. The 1st  group 8 mice  were immunized I/M with 0.1 ml of FMD vaccine, two dose with 14 days intervals, 2nd group 8 mice was inoculated I/P with 0.5 from 3x108 CFU/ml while 3rd  group was inoculated 0.2 ml of phosphate buffer saline and served as control negative. At 27-30  days post immunization, cellular immune response was done by DTH and 3 mice from each mentioned groups were sacrificed for measuring IgG titer then all the remained animals were injected I/P with 0.5 ml from infections dose3x108 CFU/ml. Post mortem examination was made at 3 days post infections and specimen of liver, kidney, lung and spleen were fixed with 10 % formalin for histopathological study. The result of skin test showed that the mean values of skin thickness against FMD vaccine at 24 hr. was 3.47 mm then increase to 4.66  at 48 hr. The result expressed high value of AB titer against FMD vaccine 2778.66 compared with control group recorded heavy bacterial growth recorded in the infected group with sever histological lesion characterized by suppurative granuloma in liver with lymphoid depletion in splenic tissue together with renal tubules degeneration while the main histopathogical findings of immunized groups revealed multiple MNCs infiltration with mature granuloma in liver and lung together with mild or absent bacterial growth. The result concluded that FMD vaccine reduce the infection in the immunized mice and enhance protective immune response against experimental murine bacterial infection.